PREVALENCE OF PRIMARY DYSMENORRHEA AND ITS RELATIONSHIP WITH BMI IN GIRLS (AGED 18-25 YEARS) OF RAWALPINDI/ISLAMABAD - Madiha Ghazanfar; Wardah Shahzad Rashid; Laiba Rafique; Muhammad Rizwan Tariq; Zahra Batool; Sabuha Saleem; Amna Rehman; Madiha Iftikhar; Amna Hameed; Maham Khalid; Nafeesa Mehmood (International Journal of Pharmacy & Integrated Health Sciences)
Background: Dysmenorrhea can be defined as painful uterine cramps that occur along with menses that affects about a fraction of menstruating women worldwide. Dysmenorrhea usually starts during or right after menarche.  Dysmenorrhea can be divided into either; Primary (pain without cause/reason) or Secondary dysmenorrhea (pelvic pain with a cause/disease), both of them are involved in painful menstrual cramps. In addition to this, symptoms such as nausea, headache, irritability and absenteeism from work and education are often reported. Objectives: This research was conducted with an aim to determine the prevalence of dysmenorrhea and to find a relation between BMI and Primary Dysmenorrhea among girls. Methodology: An observational, cross-sectional study with 351 female participants in total was performed through convenience sampling in Islamabad/Rawalpindi with a specifically designed questionnaire with slight modifications from November 2022 to January 2023. Statistics were applied using the IBM SPSS version 26.0. Results: Our research revealed a significant (p = 0.039) association between BMI and the occurrence of Primary Dysmenorrhea.  Through statistical comparisons, it was found that mild and severe dysmenorrhea symptoms were more prevalent among study participants who were underweight and those who were obese. The p-values for these comparisons were 0.000 and 0.028, respectively, indicating that underweight subjects are more likely to experience dysmenorrhea. Conclusion: Results show that the incidence of dysmenorrhea is higher in girls of age 18-25 years because of the abnormal Body Mass Index (BMI), which indicates that greater number of population have poor nutritional status and inadequate dietary habits.